The degree of practice of biology teachers for professional creativity and ethics of the teaching profession From their point of view - misanjas, Wasan Qasim Alwan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The aim of this research is to explore the level of biology teachers’ professional creativity and ethical practices from their own perspective. The research sample consisted of 127 teachers (67males and 60 females), accounting for 73.41% of the original population. These teachers were selected purposefully and taught biology to students in the fourth, fifth, and sixth grades of preparatory schools inthe Education Directorate of Maysan Governorate. The researcher employed a descriptive approach due to the nature of the study. To achieve the research objectives, two questionnaires were prepared. The first questionnaire focused on professional creativity, encompassing three domains: idea generation, problem-solving, and change. The second questionnaire focused on ethical practices in teaching and consisted of 31 items distributed across four domains: colleagues, students, school administration, and the community. The validity and reliability of both instruments were verified, and the statistical analysis package SPSS was used to extract the results, which revealed the following: 1-The level of biology teachers’ practice in preparatory schools regarding professional creativity, as perceived by the teachers themselves, was moderate across all questionnaire domains. The domains were ranked in descending order of professional creativity as follows: problem-solving, idea generation, and change. The results indicated gender differences, favoring males. The research also revealed differences based on years of experience, favoring teachers with more than 11 years of service. 2-The level of biology teachers’ practice in preparatory schools regarding ethical practices in teaching, as perceived by the teachers themselves, was moderate across all questionnaire domains. The domains were ranked in descending order of practice as follows: students, colleagues, school administration, and the community. The results indicated gender differences, favoring males. The research also revealed differences based on years of experience, favoring teachers with more than 11 years of service. The researcher recommended adopting the list of educational skills identified in this study and utilizing them by school principals and educational supervisors. Additionally, the identified educational skills should be incorporated in the training of prospective teachers.